Cardiac sympathetic afferent reflex and its implications for sympathetic activation in chronic heart failure and hypertension. (17th January 2015) - Chen, W.‐W.; Xiong, X.‐Q.; Chen, Q.; Li, Y.‐H.; Kang, Y.‐M.; Zhu, G.‐Q.
Abstract Persistent excessive sympathetic activation greatly contributes to the pathogenesis of chronic heart failure (CHF) and hypertension. Cardiac sympathetic afferent reflex (CSAR) is a sympathoexcitatory reflex with positive feedback characteristics. Humoral factors such as bradykinin, adenosine and reactive oxygen species produced in myocardium due to myocardial ischaemia stimulate cardiac sympathetic afferents and thereby reflexly increase sympathetic activity and blood pressure. The CSAR is enhanced in myocardial ischaemia, CHF and hypertension. The enhanced CSAR at least partially contributes to the sympathetic activation and pathogenesis of these diseases. Nucleus of the solitary tract (NTS), hypothalamic paraventricular nucleus (PVN) and rostral ventrolateral medulla are the most important central sites involved in the modulation and integration of the CSAR. Angiotensin II, AT1 receptors and NAD(P)H oxidase‐derived superoxide anions pathway in the PVN are mainly responsible for the enhanced CSAR in CHF and hypertension. Central angiotensin‐(1‐7), nitric oxide, endothelin, intermedin, hydrogen peroxide and several other signal molecules are involved in regulating CSAR. Blockade of the CSAR shows beneficial effects in CHF and hypertension. This review focuses on the anatomical and physiological basis of the CSAR, the interaction of CSAR with baroreflex and chemoreflex, and the role of enhanced CSAR in the pathogenesis of CHF and hypertension.